Gestión de ventas de la tienda “Baratodo” en la ciudad de Babahoyo en el periodo 2024. - Álava Costain, Cletner Alanna (2025)
The "Baratodo" store faces various problems related to its commercial management, which have negatively impacted its performance in the market. Among the main difficulties are insufficient investment in advertising and the poor promotion of its products, which has limited its ability to attract new consumers and position itself in a highly competitive market. In addition, the store has low customer loyalty, a reduced presence on social networks, intense competition from other businesses and a recurring shortage of high-demand products. To address these adversities, the Root Cause method was selected, an approach that allows for an in-depth analysis of problems from their origin, facilitating the implementation of effective, sustainable solutions aimed at business growth. Among the techniques applied, a customer survey was used, which provided valuable information about their needs, expectations and shopping experiences, and a SWOT analysis, which made it possible to evaluate the internal and external factors that influence the performance of the store, identifying strengths, weaknesses, opportunities and threats. As a result of the analysis, it was concluded that the lack of digital marketing strategies, the limited presence on social networks, the absence of online commerce platforms and an unattractive design of the physical store make it difficult to attract new customers and retain current ones. To optimize commercial management, it was proposed to increase investment in advertising, strengthen the presence in digital media, implement online shopping platforms to facilitate transactions and improve the customer experience, and adopt innovative strategies that build consumer loyalty.